Telegram - Schevenels, Walther, b. 1894
032-0193-001 F Stangate? POST OFFICE OVERSEAS TELEGRAM Official particulars, including Office of Origin. 132 PARIS 24727-33-29-1024 TRADUNIC SOWEST LDN = REFERENCE YOUR LETTER TWENTYFIFTH NOVEMBER HAVE RECEIVED REPLY FROM JOSE CASTRO VALENCIA WHO WANTS TO KNOW NAME OF SHIP STOP WOULD BE WISE ALSO SEND BILLS OF LADING PARIS : SCHEVENELS + Phoned Stolz 1-12-38. "Stangate" copies of Bills of L. being sent direct IFTU. by Scottish C.W.S. E.A.B. 292/946/32/193